2006
DOI: 10.2320/matertrans.47.1890
|View full text |Cite
|
Sign up to set email alerts
|

Hydriding Properties of (Mg<SUB>1&minus;<I>x</I></SUB>M<I><SUB>x</SUB></I>)Ni<SUB>2</SUB> C15-Type Laves Phase Alloys

Abstract: Mg-based Laves phase alloys (Mg 0:7 M 0:3 )Ni 2 , where M elements were Ca, La, Ce, Pr, Nd and Gd were successfully developed. The alloys can be synthesized by a conventional induction melting and annealing method from intermetallic compounds MgNi 2 and MNi 2 as a source of Mg, Ni and M elements. The crystal structures of the major phases of annealed (Mg 0:7 M 0:3 )Ni 2 alloys were C15-type for M ¼ Ca and C15 b -type for M ¼ La, Ce, Pr, Nd and Gd Laves structures, respectively. In the alloys except M ¼ Ce, hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Mg 1.4 Pr 0.6 Ni 4 also had the same structure, although the composition was off-stoichiometry. These results agree with previous reports for Mg 2– x RE x Ni 4 . ,,,, XRD data for Mg 1.4 Pr 0.6 Ni 4 were refined using a structure model with a cubic MgCu 4 Sn structure such that excess Mg atoms occupied the Pr site. The refined lattice constants of Mg 1.0 Pr 1.0 Ni 4 and Mg 1.4 Pr 0.6 Ni 4 were a = 7.103 (2) and 7.012 (1) Å, respectively.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Mg 1.4 Pr 0.6 Ni 4 also had the same structure, although the composition was off-stoichiometry. These results agree with previous reports for Mg 2– x RE x Ni 4 . ,,,, XRD data for Mg 1.4 Pr 0.6 Ni 4 were refined using a structure model with a cubic MgCu 4 Sn structure such that excess Mg atoms occupied the Pr site. The refined lattice constants of Mg 1.0 Pr 1.0 Ni 4 and Mg 1.4 Pr 0.6 Ni 4 were a = 7.103 (2) and 7.012 (1) Å, respectively.…”
Section: Resultssupporting
confidence: 89%
“…We have been interested in Mg-containing alloys as hydrogen storage materials for fuel cell vehicles. We have developed (Mg 0.67 Ca 0.33 )Ni 2 with a C15 structure and Mg 1.4 RE 0.6 Ni 4 (RE = Nd, Pr) with a cubic MgCu 4 Sn type structure that reversibly absorb and desorb hydrogen at room temperature. , They absorb hydrogen up to 0.5–0.7 H/M (H/M: ratio of number of hydrogen and metal atoms) via one plateau from an alloy phase to a hydride phase. , Recently, we found that Mg 1.0 Pr 1.0 Ni 4 showed two plateaus on the pressure–composition (P–C) isotherms with a total hydrogen capacity of around 1.1 H/M at 273 K, where the composition of the hydride phase corresponds to γ-Mg 1.0 Pr 1.0 Ni 4 H ∼6 . These results suggest that the hydrogenation properties of Mg 2– x Pr x Ni 4 depend on the ratio of Mg and Pr in the alloy phase.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them reversibly absorb and desorb hydrogen at ambient temperature. 6,7) The maximum hydrogen content of (Mg 0.67 Ca 0.33 )Ni 2 is 1.4 mass% (H/M = 0.7) under hydrogen pressure of 4 MPa at temperature of 278 K. We have improved plateau flatness and cycle durability of (Mg 0.67 Ca 0.33 )Ni 2 C15-type Laves phase by substituting Y for a part of Ca. 8) Hydrogenation properties of the ternary compounds MgRENi 4 (RE = La, Nd and Gd) have been reported by several groups.…”
Section: Introductionmentioning
confidence: 93%
“…One main disadvantage of ball milling method is that the sample could easily be polluted by steel balls and air, even in very good protection conditions. Other techniques that are usually used to prepare Mg-based materials include melting [2,[13][14][15][16], combustion synthesis [17][18][19], bulk mechanical alloying [20][21][22][23][24], melting spinning [25][26][27][28][29][30], replacement-diffusion method [31], rotation-cylinder [32,33], laser sintering [34], etc.…”
Section: Introductionmentioning
confidence: 99%